Theological dialogue towards ethical restoration in a homophobia-riddled society - Resane, Kelebogile T. (HTS teologiese studies, 2020)
Homosexuality and homophobia in South Africa exist side by side. Homophobia is very common in communities and churches. Biblical texts, traditional cultures and politics partner to dismiss, discredit or disqualify homosexuality, but historians and anthropologists have evidence that homosexuality has been around within African cultures for many ages. Christians are divided into two camps. There are those who openly oppose gay rights with citations from biblical texts, claiming that homosexuality is forbidden by God. Others claim that this is poor biblical scholarship and a cultural bias read into the Bible. To these, the Bible says nothing about homosexuality as an innate dimension of personality; as a sexual orientation, it was not understood in biblical times. Despite a progressive constitution and affirming legislation, sexual and gender minorities experience discrimination in South Africa. The church expresses homophobic tendencies by excluding homosexual people from the sacraments, liturgy and ordination. Theology is invited to embark on a journey of dialogue with communities and homosexual people in order for it to be meaningful and relevant and contribute towards social, political and economic empowerment. Through dialogue with the homophobic community, theology can journey out of the continuous hermeneutic circle spanning biblical text, dogmatic traditions and the present, ever-changing historical context. This journey is taken, applying the ethics of faith, hope and love.Contribution: The article invites further research on theological grounds for exclusion of same-sex orientation people from ecclesial rights such as ordinances, liturgy, confessions and ordination.